The mediating effect of brand trust on the relationship between corporate social responsibility and hotel customer satisfaction - Niu, Li; Abdullah, Zulhamri; Mahamed, Mastura; Long, Huiying (Creative Publishing House, 2024)
This study explores the impact mechanism of corporate social responsibility (CSR) on hotel customer satisfaction, paying part icular attention to the mediating role of brand trust in this process. Based on stakeholder theory and signaling theory, we propose that corporate social responsibility not only directly affects customer satisfaction, but also indirectly affects satisfaction by enhancing customer trust in the hotel brand. We surveyed 732 guests at multiple hotels and analyzed the data using structural equation modeling. The results support our theoretical model and reveal that (1) a hotel's corporate social responsibility practices have a significant positive impact on customer satisfaction; (2) brand trust partially mediates the relationship between corporate social responsibility and customer satisfaction. relationship; (3) hotel type (luxury hotel vs. budget hotel) moderates the impact of corporate social responsibility on brand trust, and this relationship is more obvious in luxury hotels. This study enriches the literature on the impact mechanism of corporate social responsibility, reveals the key role of brand trust in hotel corporate social responsibility practices, and provides a new perspective for hotel managers to improve the effectiveness of corporate social responsibility.